Isokinetic data related to rate of force development is better correlated to acceleration sprint performance than peak torque - Bertochi, G. F. A.; Puggina, E. F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Isokinetic tests are commonly used for strength assessment in athletes. Previous data support a relationship with knee strength and sprint acceleration performance [1], although not unanimous [2]. However, due to velocity component of sprint performance, is to be expected that isokinetic data associated with rapid force capacity would be better related with acceleration sprint performance (0-40 m) when compared to peak torque data. Therefore, the aim of this study was to investigate the association between isokinetic data associated with rapid force capacity or peak torque and acceleration sprint performance, and compare with traditional repetition maximum (RM) test.